Inhibitory Regulation of Rac Activation, Membrane Ruffling, and Cell Migration by the G Protein-Coupled Sphingosine-1-Phosphate Receptor EDG5 but Not EDG1 or EDG3 - Okamoto, Hiroyuki (American Society for Microbiology, 2000)
Sphingosine-1-phosphate (S1P) is a bioactive lysophospholipid that induces a variety of biological responses in diverse cell types. Many, if not all, of these responses are mediated by members of the EDG (endothelial differentiation gene) family G protein-coupled receptors EDG1, EDG3, and EDG5 (AGR16). Among prominent activities of S1P is the regulation of cell motility; S1P stimulates or inhibits cell motility depending on cell types. In the present study, we provide evidence for EDG subtype-specific, contrasting regulation of cell motility and cellular Rac activity. In CHO cells expressing EDG1 or EDG3 (EDG1 cells or EDG3 cells, respectively) S1P as well as insulin-like growth factor I (IGF I) induced chemotaxis and membrane ruffling in phosphoinositide (PI) 3-kinase- and Rac-dependent manners. Both S1P and IGF I induced a biphasic increase in the amount of the GTP-bound active form of Rac. In CHO cells expressing EDG5 (EDG5 cells), IGF I similarly stimulated cell migration; however, in contrast to what was found for EDG1 and EDG3 cells, S1P did not stimulate migration but totally abolished IGF I-directed chemotaxis and membrane ruffling, in a manner dependent on a concentration gradient of S1P. In EDG5 cells, S1P stimulated PI 3-kinase activity as it did in EDG1 cells but inhibited the basal Rac activity and totally abolished IGF I-induced Rac activation, which involved stimulation of Rac-GTPase-activating protein activity rather than inhibition of Rac-guanine nucleotide exchange activity. S1P induced comparable increases in the amounts of GTP-RhoA in EDG3 and EDG5 cells. Neither S1P nor IGF I increased the amount of GTP-bound Cdc42. However, expression of N(17)-Cdc42, but not N(19)-RhoA, suppressed S1P- and IGF I-directed chemotaxis, suggesting a requirement for basal Cdc42 activity for chemotaxis. Taken together, the present results demonstrate that EDG5 is the first example of a hitherto-unrecognized type of receptors that negatively regulate Rac activity, thereby inhibiting cell migration and membrane ruffling.